Capital Adequacy, Credit Risk, and Bank Profitability: The Moderating Role Of Operational Efficiency In Indonesian Private Commercial Banks - Theresia Tiwi; Sari Yuniarti; Nanik Sisharini; Sugeng Haryanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the relationship between Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and operational efficiency measured by the Operating Expenses to Operating Income ratio (BOPO) on profitability, represented by Return on Assets (ROA), as well as to explore the moderating role of BOPO in strengthening or attenuating the effect of NPL on ROA in National Private Commercial Banks (BUSN) in Indonesia during the period 2020–2024. A quantitative approach was employed using secondary data sourced from annual financial statements, and analysis was conducted through panel data regression to simultaneously capture temporal and cross-entity variations. Empirical results indicate that CAR and NPL have a significant negative effect on ROA, suggesting that higher capital levels or elevated credit risk tend to reduce bank profitability. Conversely, BOPO exerts a significant positive effect on ROA, implying that increases in operational expenses in BUSN are more associated with the intensification of productive activities that effectively enhance revenue rather than non-productive costs (Kasmir, 2019). Furthermore, BOPO is found to moderate the NPL-ROA relationship, emphasizing that operational efficiency and quality management of business activities are crucial determinants in mediating the impact of credit risk on profitability.